Whether and how tourism industry upgrading promotes employee social upgrading? Insights from China - Tao Lin (PLoS ONE, 2025)
In response to the decent work agenda in the United Nations Sustainable Development Goal 2030, an increasing body of studies has focused on social upgrading in developing countries. Numerous studies have explored whether and how economic upgrading promotes social upgrading in various industries and regions. However, few studies have examined the employee social upgrading resulting from the upgrading in the tourism industry. Moreover, most existing studies have adopted a qualitative approach, with limited quantitative research exploring the economic-social upgrading relationships. Using data from a survey conducted in China in 2024, this study examines whether and how tourism industry upgrading promotes social upgrading among related employees, as well as the role of governance environment in this relationship, employing a structural equation modeling (SEM) approach. The modeling results highlight the significance of tourism industry upgrading in promoting social upgrading of tourism industry employees. Additionally, the local governance environment is found to significantly moderate the relationship between tourism industry upgrading and employee social upgrading. This study contributes to the literature on economic and social upgrading by providing empirical evidence from the tourism sector and emphasizing the importance of governance in facilitating social improvements.